The code of conduct (adab) for rulers in two Malay masterpieces - Hamdan, Rahimah; Ibrahim, Siti Nor Harmiza (Human Resource Management Academic Research Society, 2019)
The aim of this paper was to explain about the code of conduct (adab) as described in the Malay literary masterpiece, the Taj Us Salatin (Mahkota Raja-Raja), and to compare it with the famous epic Malay text, the Hikayat Iskandar Zulkarnain. The Taj Us Salatin (Mahkota Raja-Raja), a well-known literary work on constitutionalism written by Bukhari Al-Jauhari, was used by the Malay rulers as a guidebook on governance, starting from the time of Sultan Alauddin Riayat Shah in Acheh in the 17th century until the time of Sultan Hussein Syah of the Johore-Singapore Sultanate in the 19th century. All the procedures of government were comprehensively recorded in this book by the author. As a result, a prominent figure, Iskandar Zulkarnain, who was both a great ruler and warrior, was said to be the first in a royal line of Malay sultans, as recorded in historiographic works. Hence, this noble figure was often highly esteemed in most of the literary works and, in fact, this manifestation was even assumed to validate the sovereignty of a kingly dynasty in the Malay World. The question is, were the guidelines for rulers, as recorded in the Taj Us Salatin, in line with the code of conduct (adab) for rulers and warriors in the epic Hikayat Iskandar Zulkarnain? Therefore, by doing a text analysis of the Taj Us Salatin (Mahkota Raja-Raja) and the Hikayat Iskandar Zulkarnain, this paper compared the connection and link in the characterisation of the code of conduct (adab) for rulers between both texts. This study makes an important contribution, especially in enhancing the contribution of the Malay masterpiece, the Taj Us Salatin (Mahkota Raja-Raja), as a constitutional literature containing highly valuable knowledge, and Iskandar Zulkarnain as a famous Malay ruler and warrior. In summary, the code of conduct (adab) of a ruler was reflected in the stability and peace that prevailed in a country, so much so that this element was given serious emphasis in most of the genres of traditional Malay literature.